Aplikasi Zeolite dari Cangkang Kelapa Sawit Pada Penyerapan Logam Kromium Heksavalen (Cr6+) Heksavalen Pada Industri Elektroplating - Lince Muis; Edwin Permana; Hasrul Anwar (Jurnal Daur Lingkungan, 2019)
Zeolite is a hydrated alumino-silicate compound having a main element which consists of alkali and alkaline-earth cations, especially Ca, K and Na, with a general formula (LmAlx Sig O2nH2O) where L is a metal. Zeolite can be synthesized from a sample containing silica and alumina. The compounds contain alkali hydroxide or organic bases. Palm kernel shells are one of the industrial wastes containing many minerals such as SiO2 58.02%; Al2O3 8.7%. The source of silica and alumina in oil palm shells is used as a base for making zeolites using the hydrothermal method in a reactor. Fine samples of palm shells were melted with NaOH at 500 °nn C for 1 hour and diluted to produce sodium silicate reactants. Making sodium aluminate reactant is done by dissolving NaOH in distilled water and then heating and adding Al(OH)3 to NaOH solution with stirring. Making zeolite is done by mixing sodium silicate and sodium aluminate reactants and the zeolite crystallization process is carried out using a hydrothermal reactor heated in the oven by varying the hydroternal temperature of 1200C, 150 ° C and 1800C for 8 hours. The synthesized zeolite was characterized using XRF, FTIR and SEM EDX.